Pay-what-you-want, identity, and self-signaling in markets - Gneezy, Ayelet; Gneezy, Uri; Riener, Gerhard; Nelson, Leif D (Proceedings of the National Academy of Sciences - PNAS, 2012)
We investigate the role of identity and self-image consideration under "pay-what-you-want" pricing. Results from three field experiments show that often, when granted the opportunity to name the price of a product, fewer consumers choose to buy it than when the price is fixed and low. We show that this opt-out behavior is driven largely by individuals' identity and self-image concerns; individuals feel bad when they pay less than the "appropriate" price, causing them to pass on the opportunity to purchase the product altogether.